Leadership Synergy of Principals and School Committees in Improving the Quality of Education: The Perspective of Elementary School Teachers - Asparingga, Ririn; Harapan, Edi; Kesumawati, Nila (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
: This study aims to analyze the leadership synergy between School Leadership Principals and School Committees in improving the quality of education from the perspective of elementary school teachers. The research employs a quantitative approach with a descriptive design. The population consists of all teachers at public elementary schools in Ilir Barat I District, Palembang, totaling 113 individuals. A sample of 88 teachers was selected using a proportional stratified random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 26.00. The results indicate that both teacher perceptions of the leadership of School Leadership Principals and the role of School Committees have a positive and significant impact on the quality of education, both individually and simultaneously. These findings highlight that synergy between visionary and participatory school principals and active school committees can serve as a strategic force in supporting the improvement of basic education quality. The implications of this study can serve as a foundation for educational policy formulation and for strengthening collaboration among school stakeholders.